Chemical Speciation of the System Cu(II)-Indomethacin in Ethanol and Water by UV-Vis Spectrophotometry - Norma Rodríguez-Laguna; Luis I. Reyes-García; Rosario Moya-Hernández; Alberto Rojas-Hernández; Rodolfo Gómez-Balderas (Journal of Chemistry)
It has been proposed that the metal-drug complexes could be in fact the active agents displaying therapeutic effects of drugs. The characterization of the global formation equilibrium of complexes formed between metal ions and species with biological activity such as nonsteroidal anti-inflammatory drugs provides essential information to understand the mechanism of action of drugs. Since equilibrium constants determine the relative predominance of species, they provide crucial information to identify what complexes are more likely to be present in the system being responsible for the therapeutic effects of the drug. In this paper, the systems formed between copper and Indomethacin of different concentrations in ethanol or water were studied by UV-Vis spectrophotometry. The stoichiometry of the complexes Cu(II)–Indomethacin and their formation constants were investigated. Moreover, molecular structures of the Cu(II)–Indomethacin complexes were explored by means of the molecular modeling within the frame of the density functional theory.